KAJIAN SOSIO-HISTORIS MAQASID AL-SHARIâAH SEBAGAI PILAR ETIKA UNIVERSAL ISLAM - Sumbulah, Umi (JURNAL PENELITIAN KEISLAMAN, 2012)
Islam revealed its characteristics as a religion that defenses against the elements of humanity. Historically, the values were applied in life since the beginning of the existence of Islam in this earth. Equality before the law, protection of society from tyranny, and protection guarantee of basic rights, are some scratches of uncontested history, from the Prophet Muhammadâs prophetic treatise that concerns with the existence of these human values. Disclosure of this fact was done through historical studies, with emphasis on the sources of the documents (relevant books), using content analysis. The results showed that the maqa>s}id al-shariâah was a strong pillar for the necessity of implementation in life, because it was inherent to the existence of Islam as a religion and civilization, as well as experimentation of Mi>tha> q Madi> nah. But the dynamics of history and politics played its part to determine the âfaceâ of the embodiment of universal values, which implies a social atmosphere.